Shirley - Bronte, Charlotte, 1816-1855. (London : Penguin, 1994)
This is a historical novel which depicts an uneasy era of Luddite riots, bad harvests and social unrest as well as Charlotte Bronte's belief that the denial of the world of feeling is responsible for much of society's suffering.
Keywords: Fiction